Structure and Connectivity of Hydrothermal Vent Communities Along the Mid-Ocean Ridges in the West Indian Ocean: A Review - Perez, Maëva; Sun, Jin; Xu, Qinzeng; Qian, Pei-Yuan (Frontiers in Marine Science, 2021)
To date, 13 biologically active hydrothermal vent (HTV) fields have been described on the West Indian Ocean ridges. Knowledge of benthic communities of these vent ecosystems serves as scientific bases for assessing the resilience of these ecosystems under the global effort to strike an elegant balance between future deep-sea mining and biodiversity conservation. This review aims to summarize our up-to-date knowledge of the benthic community structure and connectivity of these Indian Ocean HTVs and to identify knowledge gaps and key research questions to be prioritized in order to assess the resilience of these communities. The HTVs in the West Indian Ocean are home to many unique invertebrate species such as the remarkable scaly-foot snail. While distinct in composition, the macrofaunal communities of the Indian HTVs share many characteristics with those of other HTVs, including high endemism, strong zonation at the local scale, and a simple food web structure. Furthermore, Indian Ocean HTV benthic communities are mosaic compositions of Atlantic, Pacific, and Antarctic HTV fauna possibly owning to multiple waves of past colonization. Phylogeographic studies have shed new light into these migratory routes. Current animal connectivity across HTV fields appears to be highly influenced by distance and topological barriers. However, contrasting differences in gene flow have been documented across species. Thus, a better understanding of the reproductive biology of the Indian Ocean HTV animals and the structure of their population at the local scale is crucial for conservation purposes. In addition, increased effort should be given to characterizing the vents’ missing diversity (at both the meio- and micro-scale) and elucidating the functional ecology of these HTVs.